Survey Satisfaction the Teacher Development Program Through Experiential Learning Based Outbound Sports Health at Pt. Human Resource Strengthening - Nurhadi, Maha Dewi Afifah; Saryono, Saryono; Izzuddin, Deden Akbar; Gemael, Qorry Armen; Wijaya, Habibi Hadi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to identify participants' satisfaction with the teacher development program through experiential learning-based outbound in sports health at PT Human Resource Strengthening Sukses Istimewa. The research method used is a descriptive survey with a quantitative approach. Data collection in this study through instruments, namely questionnaires in the form of google forms and data assessment scales using Likert scales SS, S, N, TS, STST which have gone through validity and reliability tests. The instrument used was declared valid and highly reliable with Cronbach' Alpha of 0.821. The population used is teachers who have participated in the teacher development program, while the sampling technique of this study is purposive sampling. The results of the study indicate that the participants' level of satisfaction with the implementation of the teacher development program is included in the “very satisfied” category. It is shown by the results of data analysis which states that 87.20% of participants expressed satisfaction with the program. Thus, the program strongly supports the use of experiential learning methods in developing professional teachers